Digital Financial Innovation In SMEs: A Bibliometric Approach - Firasati, Aoliyah; Setiawan, Adi; Alwi, Muhamad; Prasetya , Budi Agung (Journal of Ecohumanism, 2025)
In the era of digitalization that continues to develop from 4.0 and will enter the era of 5.0. Conditions like this direct the trend of digital transformation for the implementation of SMEs. Studies related to financial management innovation in SMEs are needed to improve adaptation in the digital era. Many studies are needed to improve the development of science related to financial management in improving the ability to understand, predict and manage the implementation of digital financial innovation. To review the literature review, articles were collected from well-known publishers such as Elsevier, Springer, Emerald, Taylor & Francis, Wiley Online Library, proquest, ebscohost, and sage. Selected articles related to the theme of digital financial innovation in SME companies were collected as many as 953 using the Publish or Perish application. This number consists of articles published from 2005 to 2024. Mapping of the articles was carried out using bibliometric methods and scientific visualization using the VOSviewer application. Network visualization analysis shows that Fintech and Blockchain technology have the strongest total link strength. Overlay visualization analysis shows that the theme related to Digital Financial Innovation in SMEs is a new theme in the development of research trends. Density visualization analysis shows that themes related to Blockchain technology, and Fintech are frequently discussed themes. On the other hand, Financial inclusion, SME, financial literacy and digital innovation have less intensity.